Effects of polystyrene microplastics on the fitness of earthworms in an agricultural soil - Cao, Dongdong; Wang, Xiao; Luo, Xianxiang; Liu, Guocheng; Zheng, Hao (IOP conference series. Earth and environmental science, 2017)
Microplastics (MPs) pollution is widespread in the environment, while the effects of MPs on the soil organisms are poorly understood. In this study, we investigated the fitness of earthworms (E. Foetida) exposed to MPs (Polystyrene, 58 μm) in soils at the concentrations of 0, 0.25, 0.5, 1 and 2% (w/w). The results showed that MPs had little effects on the fitness of earthworms under low exposure concentrations (≤ 0.5 % (w/w)), while MPs exposure with high concentrations (i.e., 1% and 2%) significantly inhibited the growth and increased the mortality of earthworms. The results indicated that the MPs pollution in soils have an adverse effect on the fitness of soil organisms, and implied the ecological risk of MPs in terrestrial ecosystems.